Self-expandable metallic stent application for the management of upper - Emre, A; Sertkaya, M; Akbulut, S; Erbil, O; Yurttutan, N; Kale, IT; Bulbuloglu, E (2018)
Objective: The aim of the present study was to share our experiences of the use of self-expandable metallic stent for the upper gastrointestinal tract disease. Material and Methods: We retrospectively reviewed the medical records of 18 patients who underwent self-expandable metallic stent implantation procedure for anastomosis stricture, anastomosis leak, or spontaneous fistula of the upper gastrointestinal tract at two different surgery clinics. Self-expandable metallic stent implantation procedures were performed while keeping the patient under sedation and the correct stent localization was verified using fluoroscopy. The stent localization and possible stent migration were checked using X-ray films taken a few days after the stenting procedure. Results: Overall, 25 self-expandable metallic stents were implanted in 18 patients (malignant, 13; benign, 5) aged between 19 and 89 years. The indications for self-expandable metallic stent implantation were as follows: malignant gastric stricture (inoperable; n=6), malignant esophageal stricture (inoperable; n=4), staple line leak (laparoscopic sleeve gastrectomy; n=4), esophagojejunostomy anastomotic leak (total gastrectomy+Roux-en-Yesophagojejunostomy; n=2), and stricture (total gastrectomy+Roux-en-Yesophagojejunostomy; n=1), and esophagopleural fistula (pulmonary tuberculosis; n=1). A favorable outcome was achieved in a single session in 15 patients, whereas more than two sessions of stenting were necessary in the remaining three patients. Among the patients who underwent esophagojejunal anastomosis (n=3), self-expandable metallic stents were successfully deployed in a single session in two patients to relieve anastomosis leak (n=1) and anastomosis stricture (n=1); the remaining patients underwent four self-expandable metallic stent implantation procedures to relieve anastomosis leak and subsequent recurrent strictures. No complications developed during the stenting procedure. Three of the four patients who developed mortality had advanced stage esophageal cancer, whereas one patient had morbid obesity and developed staple line leakage. Conclusion: Endoscopic self-expandable metallic stent implantation under fluoroscopic guidance is a low-morbidity and effective procedure for the management of advanced stage tumors of the gastrointestinal tract and the elimination of postoperative complications. C1 [Emre, Arif; Sertkaya, Mehmet; Kale, Ilhami Taner; Bulbuloglu, Ertan] Sutcu Imam Univ, Dept Gen Surg, Sch Med, Kahramanmaras, Turkey. [Akbulut, Sami] Inonu Univ, Dept Gen Surg, Sch Med, Malatya, Turkey. [Erbil, Ozan] Gebze State Hosp, Dept Gen Surg, Izmit, Turkey. [Yurttutan, Nursel] Sutcu Imam Univ, Dept Radiol, Sch Med, Kahramanmaras, Turkey.